A Porcine Model of Laparoscopic Intersphincteric Resection for Ultra-Low Rectal Cancer - Min-Wei Zhou; Ji-Xin Ma; Zheng-Qing Yan; Zheng-Dong Qiao; Zhen-Yang Li; Xiao-Dong Gu; Sen Yan; Yi-Wen Zang; Zong-You Chen; Yi-Ming Zhou; Jian-Hua Ding; Jian-Bin Xiang (Journal of Investigative Surgery)
Objective To develop a porcine model for laparoscopic intersphincteric resection (ISR) targeting ultra-low rectal cancer.Methods Six Bama mini-pigs underwent a standard laparoscopic ISR procedure: (1) Ligation and transection of the inferior mesenteric vessels; (2) Exposure and sparing of the pelvic autonomic nerves; (3) Dissection of the rectum; (4) Dissection and transection of hiatal ligament and rectourethralis muscle; (5) Transanal dissection of the anal canal; (6) Dissection of the intersphincteric space (ISS); (7) End-to-end handsewn coloanal anastomosis (CAA). Pathological evaluations were conducted to ascertain the precision of the ISR. Furthermore, postoperative fecal incontinence scores were systematically assessed on a weekly basis throughout a 12-week post-surgery follow-up period.Results All six pigs survived surgery without conversion to an open approach. There were no occurrences of incisional infection or any surgical complications, including anastomotic leakage, anastomotic bleeding, or ileus. Postoperatively, one pig manifested constipation and three exhibited anal redness, both conditions ameliorating within a week. No erosive ulcers were detected. Notably, all animals exhibited fecal staining on their tails within the first two weeks post-surgery, transitioning to formed feces by the third week. Improvement in defecation frequency was observed after 6 weeks, with a noticeable reduction in defecation areas after one month. Incontinence scores, evaluated three months post ISR surgery, revealed no significant abnormalities in anal function compared to preoperative assessments.Conclusions This study established a replicable porcine model for laparoscopic ISR, demonstrating its potential utility in clinical and fundamental research related to ultra-low rectal cancer treatment.